Externalizing disorders in American Indians: comorbidity and a genome wide linkage analysis - Ehlers, Cindy L. (2008)
Alcohol dependence is one of the leading causes of morbidity and mortality in Native Americans. Externalizing disorders such as conduct disorder (CD) and antisocial personality disorder (ASPD) have been demonstrated to have significant comorbidity with alcohol dependence in the general population. This study’s aims were to: assess the comorbidity of DSM-III-R ASPD and CD with alcohol dependence, to map susceptibility loci for ASPD and CD, and to see if there is overlap with loci previously mapped for alcohol dependence phenotypes in 587 American Indians. Alcohol dependence was found to be comorbid with DSM-III-R ASPD but not CD. However, the amount of alcohol dependence in the population attributable to ASPD and/or CD is low. ASPD and the combined phenotype of participants with ASPD or CD were both found to have significant heritability, whereas no significant evidence was found for CD alone. Genotypes were determined for a panel of 791 micro-satellite polymorphisms in 251 of the participants. Analyses of multipoint variance component LOD scores, for ASPD and ASPD/CD, revealed six locations that had a LOD score of 2.0 or above: on chromosome 13 for ASPD and on chromosomes 1,3,4,14,17 and 20 for ASPD/CD. These results corroborate the importance of several chromosomal regions highlighted in prior segregation studies for externalizing diagnoses. These results also further identify new regions of the genome, that do not overlap with alcohol dependence phenotypes previously identified in this population, that may be unique to either the phenotypes evaluated or this population of American Indians.